Development of asphalt mixture with plastic waste additives to improve road pavement performance - Ilwandri; Insira Insani Fitri; Nanich Framulya; Titis Wulandari (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2023)
The increase in the volume of vehicular traffic leads to faster damage to road pavements. The use of additives in asphalt mixtures is believed to improve the properties of the mixture so as to increase resistance to damage. This research aims to develop an asphalt mixture by utilizing plastic waste as an additive. The plastic waste used is a type of Polyethylene (PE) and Polypropylene (PP). The test was carried out by varying the content of plastic additives in the asphalt mixture by 2%, 4%, 6%, 8% and 10% to the weight of asphalt. The asphalt mixture is tested for marshall characteristics, indirect tensile strength test, durability test, and wheel tracking test. Test results show the addition of plastic additives up to 8% increases stability, strength, durability, and resistance to deformation of asphalt mixtures. The improved performance of the mixture is thought to be due to the interaction between plastic and asphalt which results in a stronger bond. This research proves that the use of plastic waste as an additive material can be a solution to improve road pavement performance.